A gathering dilemma: The Drawing International Brisbane Symposium. Issue 2 (1st July 2016) - Platz, William; O'Dempsey, Kellie
As drawing researchers and practitioners doggedly pursue academic conferences and symposia dedicated to their discipline, it has become increasingly necessary to question the forms, structures and relevance of the academic conference to drawing research. One of the strengths of arts-based research is its incongruity with conventional systems and protocols in university culture. A lack of accordance yields forms of knowledge and reforms of codes necessary to a progressive position. In 2015, a biennial drawing research symposium was inaugurated in Brisbane, Australia titled Drawing International Brisbane (DIB). The event sought to generate a model for the academic symposium in which visual practitioners, theorists, historians, curators, students and administrators could coalesce in a productive and vigorous programme. Combining conventional academic papers, plenary sessions, exhibitions, artist's presentations and workshops, DIB produced friction, synthesis and multiplication from components that did not radically depart from established norms, but were redeployed in a motivated programme to reinvigorate the academic symposium as a meaningful environment for the production and dissemination of knowledge. An account of one of the DIB2015 Conference streams evidences the potency of this method.